2019
DOI: 10.18203/2394-6040.ijcmph20192326
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dementia in older adults using Mini-Cog scale from a rural setting of Kashmir division

Abstract: Background: Dementia is common in the geriatric population. It has been suggested that early detection leads to benefits for the patient and their family and cuts the costs. The solution to this problem lies in the development of brief and easily applicable tests that are acceptable to patients, their caregivers, and health professionals. The current study was undertaken for screening for dementia using Mini-Cog scale.Methods: Cross sectional study from District Budgam of Kashmir Division done on individuals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…10 and study done by Jan et al also revealed increased incidence of CI in females (63.2%). 11 Other studies have found a correlation between being female and an increased likelihood of experiencing CI. 12,13 During menopause, women experience a decline in hormones like oestrogen, progesterone, and testosterone.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…10 and study done by Jan et al also revealed increased incidence of CI in females (63.2%). 11 Other studies have found a correlation between being female and an increased likelihood of experiencing CI. 12,13 During menopause, women experience a decline in hormones like oestrogen, progesterone, and testosterone.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, study done by Jan et al showed increased risk of dementia in the age group of 60 to 64 years and 70 to 74 years (63%). 11 Also, study done by Rajesh et al showed that proportion of CI was higher among 70-74 years of age group (50%). 10 Our study further confirms that elderly age can be taken as primary risk factor for developing CI and the prevalence of CI increases steeply with age in elderly populations.…”
Section: Resultsmentioning
confidence: 95%